2012
DOI: 10.1158/1078-0432.ccr-11-2487
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Four miRNAs Accurately Differentiates Malignant from Benign Indeterminate Thyroid Lesions on Fine Needle Aspiration

Abstract: Purpose: Indeterminate thyroid lesions on fine needle aspiration (FNA) harbor malignancy in about 25% of cases. Hemi-or total thyroidectomy has, therefore, been routinely advocated for definitive diagnosis. In this study, we analyzed miRNA expression in indeterminate FNA samples and determined its prognostic effects on final pathologic diagnosis.Experimental Design: A predictive model was derived using 29 ex vivo indeterminate thyroid lesions on FNA to differentiate malignant from benign tumors at a tertiary r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
122
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 40 publications
4
122
0
2
Order By: Relevance
“…MiR-197 was found to be overexpressed in lung, prostate and pancreas cancer tissues compared with normal specimen, [17][18][19] while levels of circulating miR-197 in combination with other miRNAs were used to generate a signature of biomarkers for early detection of lung cancer. 20,21 Moreover, increased expression of miR-197 contributes to carcinogenesis and it is considered a reliable marker for diagnosis, patient stratification and prognosis assessment in follicular thyroid carcinomas, [22][23][24] while promoting EMT and metastasis in pancreatic adenocarcinoma. Supported by these in vitro results, we hypothesized that miR-197 targeting may exert a therapeutic activity by inhibiting tumor growth in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-197 was found to be overexpressed in lung, prostate and pancreas cancer tissues compared with normal specimen, [17][18][19] while levels of circulating miR-197 in combination with other miRNAs were used to generate a signature of biomarkers for early detection of lung cancer. 20,21 Moreover, increased expression of miR-197 contributes to carcinogenesis and it is considered a reliable marker for diagnosis, patient stratification and prognosis assessment in follicular thyroid carcinomas, [22][23][24] while promoting EMT and metastasis in pancreatic adenocarcinoma. Supported by these in vitro results, we hypothesized that miR-197 targeting may exert a therapeutic activity by inhibiting tumor growth in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…As a small molecule, it is relatively stable in FNA specimens and in formalin-fixed, paraffin-embedded cell-block materials and is, therefore, amenable to detection. Specific microRNA profiles (panels) have been identified in a variety of tumors, and their diagnostic utility has also been explored in thyroid neoplasms, including FNA indeterminate lesions [37][38][39][40][41] (Table). The panels are usually small, consisting of 2 to 4 microRNAs, and their sensitivity, specificity, and accuracy are improving as different studies on microRNAs become available.…”
Section: Microrna Profilingmentioning
confidence: 99%
“…The panels are usually small, consisting of 2 to 4 microRNAs, and their sensitivity, specificity, and accuracy are improving as different studies on microRNAs become available. Keutgen et al 40 found that a panel of 4 microRNAs consisting of miR-222, miR-328, miR-197, and miR-21 classified thyroid indeterminate lesions into benign and malignant with 100% sensitivity, 86% specificity, and 90% accuracy in a cohort of 72 cases. Further analysis indicated that the panel was suboptimal for HcN, and when 13 of those cases were excluded from the previous study, the sensitivity and accuracy were increased to 100% and 95%, respectively.…”
Section: Microrna Profilingmentioning
confidence: 99%
“…В нескольких недавних публикациях отечественных и зарубежных авторов был отчетливо продемонстри-рован потенциал диагностических методов, основан-ных на анализе малых регуляторных РНК (микроРНК) ткани узлов щитовидной железы [5][6][7]. Было показано, например, что экспрессия некоторых микроРНК спец-ифично повышается при малигнизации ткани узла [5,6] или достоверно отличается при различных гистоло-гических вариантах опухоли [8].…”
unclassified
“…Было показано, например, что экспрессия некоторых микроРНК спец-ифично повышается при малигнизации ткани узла [5,6] или достоверно отличается при различных гистоло-гических вариантах опухоли [8]. Кроме того, известно, что опухолевые клетки секретируют специфический набор микроРНК в составе мембранных везикул, так называемых экзосом.…”
unclassified